2015
DOI: 10.1292/jvms.15-0029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of amyloid deposition in mature healthy chickens in the flock that previously had outbreaks of vaccine-associated amyloidosis

Abstract: Avian amyloid A (AA) amyloidosis is commonly observed in adult birds with chronic inflammation, such as that caused by bacterial infection. We previously described vaccine-associated AA amyloidosis in juvenile chickens. In this study, the prevalence of amyloid deposition was measured in mature healthy chickens that survived a previous outbreak of avian AA amyloidosis while they were juveniles. Herein, we analyzed the amyloid deposition in mature chickens and compared the prevalence of amyloid deposition with j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…Transmission of amyloidosis from animals to humans may be possible as it has been shown previously that AA-amyloidosis can be transmitted orally within and between species (Murakami et al, 2013a(Murakami et al, , 2013b or similar to prion diseases, through a seeding-nucleation process . Transmission of amyloidosis from animals to humans has been a concern in recent years and although it has not yet been confirmed, it should be considered a public health issue (Benditt & Eriksen, 1977;Higuchi, 2013;Murakami et al, 2013a;Murakami et al, 2013b;Ibi et al, 2015). Amyloid fibril deposition was detected in the liver, spleen, duodenum, and at the injection sites as reported previously (Murakami et al, 2013a(Murakami et al, , 2013b.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Transmission of amyloidosis from animals to humans may be possible as it has been shown previously that AA-amyloidosis can be transmitted orally within and between species (Murakami et al, 2013a(Murakami et al, , 2013b or similar to prion diseases, through a seeding-nucleation process . Transmission of amyloidosis from animals to humans has been a concern in recent years and although it has not yet been confirmed, it should be considered a public health issue (Benditt & Eriksen, 1977;Higuchi, 2013;Murakami et al, 2013a;Murakami et al, 2013b;Ibi et al, 2015). Amyloid fibril deposition was detected in the liver, spleen, duodenum, and at the injection sites as reported previously (Murakami et al, 2013a(Murakami et al, , 2013b.…”
Section: Discussionsupporting
confidence: 60%
“…In spontaneous outbreaks of AA amyloidosis in flocks, the morbidity rate is between 1 and 4% but may increase to 20% (Landman et al, 1994). Other researchers have reported that the mortality rate in flocks can be up to 2% (Murakami et al, 2013a;Ibi et al, 2015). Bacterial oil-emulsion vaccines have been associated with systemic amyloidosis in chickens, and they are strongly suspected as a cause of outbreaks in flocks but this has not yet been confirmed experimentally (Von Rampin et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The avian liver can be affected by multiple conditions or etiologies. Among the non-infectious causes, there are degenerative changes, such as hydropic, glycogenic and fatty degeneration; metabolic disorders such as hemosiderosis (Abdul-Aziz & Fletcher 2016), amyloidosis (Murakami et al 2013b, Ibi et al 2015, Carnaccini et al 2016, urate deposition (Crespo & Shivaprasad 2013), fatty liver and hemorrhagic liver syndrome (Mete et al 2013, Trott et al 2014, as well as circulatory disorders (Abdul-Aziz & Fletcher 2016), and primary neoplasms such as hepatocellular adenoma, hepatocellular carcinoma, cholangioma and cholangiocarcinoma (Abdul-Aziz & Fletcher 2016, Williams et al 2020. In addition to these, the liver is also affected by neoplasms of infectious etiology, such as in Marek's disease (MD), lymphoid leukosis and reticuloendotheliosis viruses (Abdul-Aziz & Fletcher 2016).…”
Section: Introductionmentioning
confidence: 99%